Role of boundaries in control of deformation rate and strength of crystalline materials - Blum, Wolfgang (Materials Science Forum, 2009)
Plastic deformation of crystalline materials is not controlled by interaction among free dislocations only, but the interaction of free dislocations with internal boundaries. i) Low-angle boundaries: Modeling of deformation of pure materials with conventional grain size on the basis of structure evolution indicates that low-angle boundaries act as obstacles of free dislocations. The migration of the low-angle boundaries constitutes an essential recovery process determining the deformation resistance in the steady state. ii) High-angle boundaries: Severe plastic deformation transforms low-angle boundaries into high-angle ones. They differ in obstacle and recovery characteristics from low-angle boundaries, which explains the special properties of ultrafine-grained and nanocrystalline materials with regard to strength, strain rate sensitivity and ductility. iii) Phase boundaries in Ni-base superalloys enhance the strengthening by hard phases with strengthening by dense dislocation networks serving to reduce coherency stresses. It is concluded that internal boundaries play a crucial role in controlling the evolution of structure and strength in crystalline materials. © (2009) Trans Tech Publications.
Created from Fastlane, Scopus look-up
Keywords: Annihilation of dislocations; Creep rate; Deformation resistance; Dislocation structure; Flow stress; Generation of dislocations; High-angle boundaries; Low-angle boundaries; Nanostructured materials; Phase boundaries; Steady state deformation